Understanding African music -- Listen and learn: music made easy -- For future generations: Hugh Tracey and the International Library of African Music -- Sound of Africa -- Music of Africa -- Historical recordings by Hugh Tracey -- ILAM and Ubuntu Publishing -- The Dhow Countries Music Academy: Zanzibar (International Library of African Music, 2017)
pages: 182-189
Keywords: African Music